Innovation designs of industry 4.0 based solid waste management: Machinery and digital circular economy - Cheah C.G.; Chia W.Y.; Lai S.F.; Chew K.W.; Chia S.R.; Show P.L. (Academic Press Inc., 2023)
design; innovation; machinery; solid waste; waste management; article; artificial intelligence; big data; cloud computing; economic aspect; human; internet of things; machine learning; radiofrequency identification; solid waste; solid waste management; systematic review; waste management; wireless communication; worker; artificial intelligence; industry; machine learning; solid waste; waste management; Artificial Intelligence; Humans; Industry; Machine Learning; Solid Waste; Waste Management